Preface of the 8th Mechanical Engineering, Science and Technology International Conference (MEST 2024) - Noor Hanita Abdul Majid; Agus Dwi Anggono; Waluyo Adi Siswanto; Tri Widodo Besar Riyadi; Nur Rahmawati Syamsiyah; Afif Faishal; Mohammad Sukri Mustapa (Engineering Proceedings, 2025)
The 8th Mechanical Engineering, Science and Technology (MEST) Conference was held at the Universiti Muhammadiyah Malaysia, Bangunan Wisma MAIPs, Blok S1, Kompleks Desa Siswa, Uniciti Alam, 02100 Padang Besar, Perlis, Malaysia on 11–12 December 2024 [...]